Incarceration and human rights : The Oxford Amnesty Lectures - Mccarthy, Melissa (Book collections on Project MUSE., 2016)
A collection of essays and responses from diverse contributors united in original examination of the intersection between incarceration and human rights. What do human rights concerns dictate about the practices that we tolerate in places of incarceration? And conversely, what can prisons, their hard facts and the ideas underpinning them, tell us about human rights? The book offers a diversity of voices: from the inside view of Her Majesty's Inspector of Prisons to the words of a poet and former political prisoner; from an international policy overview of abuses of the mentally ill to a socio-